Is Shale Development Drilling Holes in the Human Capital Pipeline? - Dan S. Rickman; Hongbo Wang; John V. Winters (Institute for the Study of Labor (IZA), 2016)
Using the Synthetic Control Method (SCM) and a novel method for measuring changes in educational attainment we examine the link between educational attainment and shale oil and gas extraction for the states of Montana, North Dakota, and West Virginia. The three states examined are economically-small, relatively more rural, and have high levels of shale oil and gas reserves. They also are varied in that West Virginia is intensive in shale gas extraction, while the other two are intensive in shale oil extraction. We find significant reductions in high school and college attainment among all three states' initial residents because of the shale booms.
Keywords: Q4; R1; R2; 330; shale development; synthetic control method; educational attainment